Titanium silicalite molecular sieve, preparation method thereof and application of titanium silicalite molecular sieve in catalytic organic matter reaction
By preparing specific titanium silicon molecular sieve, the problem of difficult mutual soluble organic substrate and hydrogen peroxide in the catalytic reaction of titanium silicon molecular sieve is solved, the effect of reducing solvent use and energy consumption is achieved, and catalytic activity and reaction efficiency are improved.
Patent Information
- Application Number
- CN202311416169.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-10-27
- Publication Date
- 2025-04-29
AI Technical Summary
In the reaction catalyzed by titanium silicon molecular sieve, the reaction effect is poor because the organic substrate and hydrogen peroxide are difficult to dissolve, and a large amount of solvent is required to promote the reaction, which increases energy consumption and the generation of by-products.
By preparing a new titanium silicon molecular sieve, the presence of specific resonance signal peaks in the 1H MAS NMR spectrum of the molecular sieve ensures that it is suitable for reactions in which the oil and aqueous materials exist simultaneously, and promotes the diffusion of reactant molecules close to the active center.
The solvent usage is reduced, energy consumption and material consumption are reduced, the catalytic reaction cost is reduced, and the activity of titanium silicon molecular sieve in catalytic reaction is improved.
Smart Images

Figure CN119898780A_ABST
Abstract
Description
Technical Field
[0001] The present disclosure relates to the technical field of inorganic material preparation, and in particular, to a titanium silicon molecular sieve and a preparation method thereof and application thereof in catalyzing organic reactions. Background Art
[0002] Molecular sieves have high activity and product selectivity in many reactions due to their unique pore structure and active centers. Inserting titanium into the molecular sieve framework has opened up a new way to activate hydrogen peroxide and catalyze the conversion of organic matter under mild conditions. Among them, the discovery of TS-1 molecular sieve has laid the foundation for the development of new technologies for many oxidation reactions involving hydrogen peroxide, such as propylene epoxidation, cyclohexanone ammoximation, phenol hydroxylation, and thioether oxidation.
[0003] However, in the reaction catalyzed by titanium silicalite, since most organic substrates have poor solubility in water, when hydrogen peroxide is used as an oxidant, the organic substrate and hydrogen peroxide are difficult to dissolve in each other, and it is difficult to achieve a good reaction effect. Therefore, it is usually necessary to add a large amount of solvent to make the reaction system homogeneous and then contact and react with the titanium silicalite. For example, in the epoxidation reaction of propylene and hydrogen peroxide, methanol is used as a solvent; in the reaction of cyclohexanone with ammonia water and hydrogen peroxide to prepare cyclohexanone oxime, tert-butanol is used as a solvent. The large amount of solvent used, on the one hand, leads to the need to consume a lot of energy to separate the solvent during the product separation process. At the same time, the solvent may also participate in the reaction to produce by-products, such as methanol reacting with the product propylene oxide to produce propylene glycol methyl ether.
[0004] In the prior art, the surface of titanium silicon molecular sieve is mainly silanized to be lipophilic and hydrophilic (e.g. CN115724439A), so that the modified titanium silicon molecular sieve has better dispersion performance in the oil-water reaction system, and the reaction molecules are more likely to diffuse close to the active center of the catalyst. However, this method uses expensive silanization agents, the operation process is relatively complicated, and the surface grafted silanization agents are easy to fall off as the reaction time increases, which is not conducive to maintaining high performance for a long time. Summary of the invention
[0005] The purpose of the present disclosure is to provide a titanium silicate molecular sieve and a preparation method thereof and an application in catalyzing organic reactions, which can effectively improve the activity of the titanium silicate molecular sieve catalyst in the contact reaction of oil and water materials, reduce the use of solvents, and reduce energy and material consumption.
[0006] In order to achieve the above-mentioned object, the present disclosure provides a titanium silicon molecular sieve in the first aspect. 1 In the HMAS NMR spectrum, signal peaks exist at 1.68±0.15 ppm and 1.13±0.15 ppm.
[0007] Optionally, the titanium silicate molecular sieve has the following1 H MAS NMR characteristics:
[0008] The titanium silicate molecular sieve 1 The peak intensity of the signal peak at 1.68±0.15 ppm in the H MAS NMR spectrum is recorded as I 1.68 , the titanium silicalite 1 The peak intensity of the signal peak at 1.13±0.15 ppm in the H MAS NMR spectrum is recorded as I 1.13 , the titanium silicalite molecular sieve I 1.68 / I 1.13 The value of is any value in the range of 1.5 to 6.0, more preferably any value in the range of 2.0 to 4.5, and more preferably any value in the range of 2.5 to 4.0;
[0009] Optionally, the titanium silicalite molecular sieve 1 In the H MAS NMR spectrum, a signal peak is also present at the position of 1.96±0.15 ppm, and a signal peak is optionally present or absent at the position of 0.7±0.15 ppm.
[0010] Optionally, the molar ratio of silicon element to titanium element in the titanium silicalite is preferably 1:(0.001-0.1), preferably 1:(0.008-0.05), and further preferably 1:(0.013-0.025).
[0011] Optionally, the average particle size of the titanium silicate molecular sieve is 50 to 900 nm, preferably 150 to 600 nm; the BET specific surface area is 340 to 550 m 2 / g, preferably 410 to 480 m 2 / g; total pore volume is 0.14~0.7cm 3 / g, preferably 0.18 to 0.39 cm 3 / g;
[0012] Optionally, the configuration of the titanium silicalite molecular sieve is selected from one or more of MFI, MEL, BEA, MWW, and SVR; preferably, the configuration of the titanium silicalite molecular sieve is MFI.
[0013] The second aspect of the present disclosure provides a method for preparing titanium silicon molecular sieve, comprising the following steps: S1, mixing a silicon source, a titanium source, a first template and water, and performing a first hydrothermal treatment to obtain a first slurry; performing a first solid-liquid separation treatment on the first slurry, and then performing a first roasting treatment on the obtained solid product to obtain a molecular sieve intermediate product;
[0014] S2, mixing the molecular sieve intermediate product, the second template, the auxiliary agent and water, and performing a second hydrothermal treatment to obtain a second slurry; performing a second solid-liquid separation treatment on the second slurry, and then performing a second roasting treatment on the obtained solid product;
[0015] The auxiliary agent is selected from cyclic compounds having 3 to 6 carbon atoms, the cyclic compound further contains oxygen atoms, and the ratio of the number of carbon atoms to oxygen atoms in the cyclic compound is 2 or less.
[0016] Optionally, in step S1, the molar ratio of silicon source: titanium source: first template: water is 1: (0.001-0.10): (0.05-0.30): (10-40), preferably 1: (0.01-0.04): (0.10-0.25): (15-30), preferably 1: (0.015-0.03): (0.15-0.20): (18-25); wherein the silicon source is calculated as SiO2 and the titanium source is calculated as TiO2.
[0017] Optionally, the first template and the second template are each independently selected from one or more compounds having a structure represented by the following formula (M-1):
[0018] wherein R1, R2, R3 and R4 are each independently selected from an alkyl group having 2 to 4 carbon atoms and an alkenyl group having 2 to 4 carbon atoms;
[0019] Preferably, in formula (M-1), R1, R2, R3 and R4 are each independently selected from an alkyl group having 3 carbon atoms or an alkenyl group having 3 carbon atoms;
[0020] Further preferably, the first template and the second template are each independently selected from one or more of tetrapropylammonium hydroxide, allyltripropylammonium hydroxide, acryltripropylammonium hydroxide, diallyldipropylammonium hydroxide, diallyldipropylammonium hydroxide, allylpropenyldipropylammonium hydroxide, diallylpropenylpropylammonium hydroxide, diallylallylpropylammonium hydroxide, triallylpropylammonium hydroxide, tripropenylpropylammonium hydroxide, tetraallylammonium hydroxide and tetraallylammonium hydroxide; preferably one or more selected from tetrapropylammonium hydroxide, allyltripropylammonium hydroxide, acryltripropylammonium hydroxide, allylpropenyldipropylammonium hydroxide, triallylpropylammonium hydroxide and tetraallylammonium hydroxide; further preferably one or more selected from tetrapropylammonium hydroxide, allyltripropylammonium hydroxide and acryltripropylammonium hydroxide.
[0021] Optionally, the silicon source is selected from at least one of organic silicon esters, solid silica gel, white carbon black and silica sol; preferably at least one of organic silicon esters;
[0022] Optionally, the organic silicon ester is selected from one or more compounds having a structure represented by the following formula (M-2):
[0023]
[0024] Among them, R a , R b , R c and R d Each is independently selected from an alkyl group having 1 to 4 carbon atoms, wherein the alkyl group is a branched or straight chain alkyl group; preferably, the R a , R b , R c and R d Each is independently selected from methyl, ethyl, n-propyl, isopropyl, n-butyl, sec-butyl, isobutyl or tert-butyl; further preferably, the organosilicon ester is selected from one or more of tetramethyl silicate, tetraethyl silicate, tetrabutyl silicate and dimethyl diethyl silicate; further preferably, it is selected from one or more of tetramethyl silicate, tetraethyl silicate and dimethyl diethyl silicate;
[0025] Optionally, the titanium source is selected from one or more of an organic titanium source and an inorganic titanium source;
[0026] Preferably, the organic titanium source is a titanium-containing organic acid ester, and the titanium-containing organic acid ester is selected from one or more compounds having a structure represented by the following formula (M-3):
[0027]
[0028] Among them, R e , R f , R g and R h are each selected from an alkyl group having 1 to 6 carbon atoms, preferably a straight-chain alkyl group having 1 to 4 carbon atoms and a branched-chain alkyl group having 3 to 6 carbon atoms, and more preferably R e , R f , R g and R h are independently selected from a straight chain alkyl group having 2 to 4 carbon atoms and a branched chain alkyl group having 2 to 4 carbon atoms; optionally, R e , R f , R g and R h Each of the following groups is independently selected from one of methyl, ethyl, n-propyl, isopropyl, n-butyl, sec-butyl, isobutyl, tert-butyl, isopentyl, hexyl and isohexyl; preferably each of the following groups is independently selected from one of ethyl, n-propyl, isopropyl, n-butyl, sec-butyl, isobutyl and tert-butyl;
[0029] Preferably, the inorganic titanium source is selected from one or more of titanium tetrachloride, titanium trichloride, titanyl sulfate, titanocene dichloride, fluorotitanic acid and ammonium fluorotitanate;
[0030] Further preferably, the titanium source is selected from one or more of tetraethyl titanate, tetrapropyl titanate and tetrabutyl titanate.
[0031] Optionally, in step S1, the conditions of the first hydrothermal treatment include: the hydrothermal temperature is 150°C to 200°C, the hydrothermal time is 2h to 100h, and the hydrothermal crystallization pressure is the autogenous pressure; preferably, the hydrothermal temperature is 160°C to 190°C, and the hydrothermal crystallization time is 4h to 80h; further preferably, the hydrothermal temperature is 165°C to 188°C, and the hydrothermal crystallization time is 5h to 40h;
[0032] Optionally, before the first hydrothermal treatment, the method further comprises: performing a hydrolysis-to-alcohol removal treatment on a raw material mixture obtained by mixing the silicon source, the titanium source, the first template and water; Optionally, the conditions of the hydrolysis-to-alcohol removal treatment include: treating at 5°C to 120°C for 0.5h to 48h; preferably treating at 50°C to 100°C for 1h to 24h;
[0033] Optionally, the conditions of the first calcination treatment include: a calcination temperature of 300°C to 800°C, and a calcination time of 0.5h to 24h; preferably, the calcination temperature is 400°C to 600°C, and the calcination time is 2h to 12h; and the calcination atmosphere is one of air, oxygen-enriched air and oxygen-deficient air.
[0034] Optionally, in step S2, the weight ratio of the molecular sieve intermediate product: the second template: the auxiliary agent: water is 1: (0.05-0.50): (0.0001-0.005): (1-10), preferably 1: (0.15-0.45): (0.0005-0.002): (2-6).
[0035] Optionally, in step S2, the auxiliary agent is selected from one or more of trioxymethylene, tetraoxymethylene, 1,3-dioxolane, 1,4-dioxane, glycerol formal and propylene glycol formal; preferably selected from one or more of trioxymethylene, tetraoxymethylene, 1,3-dioxolane, 1,4-dioxane and glycerol formal; more preferably selected from one or more of trioxymethylene, 1,3-dioxolane and glycerol formal.
[0036] Optionally, in step S2, the conditions of the second hydrothermal treatment include: temperature of 150°C to 200°C, time of 2h to 72h, and pressure of autogenous pressure; preferably, temperature of 160°C to 180°C, time of 12h to 48h;
[0037] Optionally, the conditions of the second calcination treatment include: a calcination temperature of 350°C to 800°C, and a calcination time of 0.5h to 24h; preferably, a calcination temperature of 450°C to 600°C, and a calcination time of 1h to 8h; and a calcination atmosphere selected from one of air, oxygen-enriched air and oxygen-deficient air.
[0038] A third aspect of the present disclosure provides a titanium silicon molecular sieve prepared according to the method described in the second aspect of the present disclosure.
[0039] The fourth aspect of the present disclosure provides the use of the titanium silicon molecular sieve described in the first aspect or the third aspect of the present disclosure in catalyzing organic reactions.
[0040] Through the above technical scheme, the present invention provides a titanium silicon molecular sieve and a preparation method thereof and an application thereof in organic matter reaction. 1 In the H MAS NMR spectrum, resonance signal peaks exist at 1.68±0.15 and 1.13±0.15 ppm, which can ensure that the titanium silicate molecular sieve provided by the present disclosure is suitable for reactions in which oil phase and water phase materials exist at the same time, which is conducive to the diffusion of reactant molecules close to the active center, thereby reducing the amount of solvent used, reducing energy consumption and material consumption, and reducing the cost of catalytic reaction. The preparation method of the titanium silicate molecular sieve provided by the present disclosure is simple, easy to implement, and low in cost.
[0041] Other features and advantages of the present disclosure will be described in detail in the following detailed description. BRIEF DESCRIPTION OF THE DRAWINGS
[0042] The accompanying drawings are used to provide a further understanding of the present disclosure and constitute a part of the specification. Together with the following specific embodiments, they are used to explain the present disclosure but do not constitute a limitation of the present disclosure. In the accompanying drawings:
[0043] Figure 1 The titanium silicon molecular sieve TS-1 prepared in Comparative Example 2 1 H MAS NMR spectrum;
[0044] Figure 2 The titanium silicon molecular sieve HTS prepared in Comparative Example 3 1 H MAS NMR spectrum;
[0045] Figure 3 The titanium silicon molecular sieve TS-1-A prepared in Example 1 1 H MAS NMR spectrum;
[0046] Figure 4 The titanium silicon molecular sieve TS-1-C prepared in Example 3 1 H MAS NMR spectrum;
[0047] Figure 5 The titanium silicon molecular sieve TS-1-E prepared in Example 5 1 H MAS NMR spectrum;
[0048] Figure 6 This is the XRD spectrum of the titanium silicon molecular sieve TS-1-A prepared in Example 1. DETAILED DESCRIPTION
[0049] The specific embodiments of the present disclosure are described in detail below. It should be understood that the specific embodiments described herein are only used to illustrate and explain the present disclosure, and are not used to limit the present disclosure.
[0050] The first aspect of the present disclosure provides a titanium silicon molecular sieve. 1 In the H MAS NMR spectrum, signal peaks were present at 1.68±0.15 ppm and 1.13±0.15 ppm.
[0051] The present invention discloses a titanium silicon molecular sieve. 1 In the H MAS NMR spectrum, resonance signal peaks exist at 1.68±0.15 and 1.13±0.15 ppm, which can ensure that the titanium silicate molecular sieve provided by the present disclosure is suitable for reactions in which oil phase and water phase materials exist at the same time, which is conducive to the diffusion of reactant molecules close to the active center, thereby reducing the amount of solvent used, reducing energy consumption and material consumption, and reducing the cost of catalytic reaction. The preparation method of the titanium silicate molecular sieve provided by the present disclosure is simple, easy to implement, and low in cost.
[0052] According to the present disclosure, titanium silicate molecular sieve 1 In the H MAS NMR spectrum, the resonance absorption peak at 1.68±0.15ppm (e.g., 1.7ppm) is the Si-OH signal peak, and the resonance absorption peak at 1.92±0.15ppm (e.g., 1.9ppm) is the resonance signal peak of hydrogen bonding between Si-OH and Ti-OH. The resonance signal peaks at lower fields are signal peaks of different hydrogen bonding effects, while the signal peaks at higher fields are rarely detected and have no clear explanation. The present invention successfully prepares Ti-Ti-O-S by a new preparation method. 1 The H MAS NMR spectrum has a new characteristic signal peak located at 1.13±0.15 ppm in the high field of the titanium silicate. At the same time, due to the appearance of the new characteristic peak, the prepared titanium silicate has good catalytic performance in the catalytic reaction containing both oil phase and water phase raw materials, and the use of solvent can be reduced.
[0053] Generally speaking, silicon-aluminum molecular sieves have strong hydrophilicity due to the presence of a large number of hydroxyls or coordinated cations, while titanium-silicon molecular sieves and all-silicon molecular sieves have stronger lipophilicity due to the lack of metal cations that balance the charge with the framework aluminum and a large number of surface hydroxyls. When titanium-silicon molecular sieves are used in reactions containing both oil-phase and water-phase raw materials, since titanium-silicon molecular sieves have good lipophilicity and the oil and water in the reaction are not miscible, it is difficult for the water-phase raw materials to diffuse close to the active center, so a large amount of solvent needs to be added to dissolve them in each other to promote the reaction. For example, in the reaction of propylene and hydrogen peroxide catalyzed by titanium-silicon molecular sieves, since propylene and hydrogen peroxide are not miscible, a large amount of methanol needs to be added to dissolve them in order to achieve a better reaction effect. In industry, separating methanol requires a large amount of energy consumption, which increases costs. For another example, in the reaction of cyclohexanone ammoximation catalyzed by titanium-silicon molecular sieves, cyclohexanone and hydrogen peroxide are not miscible, and a large amount of tert-butanol needs to be added to dissolve them in each other to achieve a better reaction effect. Industry also requires a large amount of energy consumption to separate tert-butanol solvents. However, the titanium silicalite molecular sieve provided by the present disclosure has a new characteristic nuclear magnetic hydrogen spectrum signal, and the inventors of the present disclosure surprisingly found that its generation is conducive to the diffusion and reaction of oil phase and water phase raw materials to the active center.
[0054] In a preferred embodiment, the titanium silicon molecular sieve has the following 1 H MAS NMR characteristics:
[0055] The titanium silicate molecular sieve 1 The peak intensity of the signal peak at 1.68±0.15 ppm in the H MAS NMR spectrum is recorded as I 1.68 , the titanium silicalite 1 The peak intensity of the signal peak at 1.13±0.15 ppm in the H MAS NMR spectrum is recorded as I 1.13 , the titanium silicalite molecular sieve I 1.68 / I 1.13 The value of is any value in the range of 1.5 to 6.0, more preferably any value in the range of 2.0 to 4.5, and more preferably any value in the range of 2.5 to 4.0. 1.68 / I 1.13 When the value of is within the optimized range provided in this embodiment, the titanium silicon molecular sieve is more conducive to the diffusion and reaction of oil phase and water phase raw materials to the active center. In the present disclosure, signal intensity refers to the peak height value after deducting the spectrum baseline.
[0056] In a preferred embodiment, the titanium silicalite molecular sieve 1 In the H MAS NMR spectrum, there may be a resonance signal peak at 1.96±0.15 ppm, and there may or may not be a resonance signal peak at 0.7±0.15 ppm. 1The peak intensity of the signal peak at 1.96±0.15 ppm in the H MAS NMR spectrum is recorded as I 1.96 , then the titanium silicalite molecular sieve provided by the present disclosure has 1.96 / I 1.68 The value can be 0.5 to 1.5, for example, 0.5 to 0.95, 0.95 to 1.5, or 1.1 to 1.3. The resonance absorption peak at 1.96±0.15ppm in the titanium silicon molecular sieve is the resonance signal peak of hydrogen bonding between Si-OH and Ti-OH. Its existence indicates that the active center is in an activatable state, which is beneficial to shorten the induction period of the reaction. 1 The peak intensity of the signal peak at 0.7±0.15 ppm in the H MAS NMR spectrum is recorded as I 0.7 , then the I of the titanium silicalite 0.7 / I 1.13 The value of can be 0 to 0.8. In the present disclosure, the "resonance signal peak exists" means that there is a point in the spectrum within the chemical shift range where the first-order derivative is equal to zero and the second-order derivative is less than zero.
[0057] In one embodiment, the molar ratio of silicon element to titanium element in the titanium silicalite is preferably 1:(0.001-0.1), preferably 1:(0.008-0.05), and more preferably 1:(0.013-0.025).
[0058] The titanium silicon molecular sieve provided by the present disclosure may or may not contain a mesoporous structure, its low-temperature nitrogen adsorption-desorption curve may or may not have a hysteresis loop, and its TEM image may or may not have an intracrystalline hollow structure.
[0059] In a specific embodiment, the average particle size of the titanium silicate molecular sieve is 50 to 900 nm, preferably 150 to 600 nm; the BET specific surface area is 340 to 550 m 2 / g, preferably 410 to 480 m 2 / g; total pore volume is 0.14~0.7cm 3 / g, preferably 0.18 to 0.39 cm 3 / g.
[0060] In a specific embodiment, the configuration of the titanium silicalite molecular sieve is selected from one or more of MFI, MEL, BEA, MWW, and SVR; preferably, the configuration of the titanium silicalite molecular sieve is MFI;
[0061] Preferably, the titanium silicalite molecular sieve has a relative crystallinity of 40% or more, preferably 50% or more, more preferably 60% or more, further preferably 80% or more, and most preferably 85% or more, compared with an all-silicon molecular sieve of corresponding structure.
[0062] In the present disclosure, the titanium silicon molecular sieve provided by the present disclosure can be used as a catalytic active component, and its unique skeleton elements can be used, or it can be used as a carrier to further load active centers, or it can be prepared into a catalyst by mechanical mixing, kneading, tableting, extrusion, spraying, rolling ball, oil column, etc. with other catalysts, co-catalysts, structural additives, electronic additives, binders, inert carriers, etc. The reagents and preparation processes used can all be conventional reagents or processes in the art.
[0063] The second aspect of the present disclosure provides a method for preparing titanium silicon molecular sieve, comprising the following steps:
[0064] S1, mixing a silicon source, a titanium source, a first template and water, and performing a first hydrothermal treatment to obtain a first slurry; performing a first solid-liquid separation treatment on the first slurry, and then performing a first roasting treatment on the obtained solid product to obtain a molecular sieve intermediate product;
[0065] S2, mixing the molecular sieve intermediate product, the second template, the auxiliary agent and water, and performing a second hydrothermal treatment to obtain a second slurry; performing a second solid-liquid separation treatment on the second slurry, and then performing a second roasting treatment on the obtained solid product;
[0066] The auxiliary agent is selected from cyclic compounds having 3 to 6 carbon atoms, the cyclic compound further contains oxygen atoms, and the ratio of the number of carbon atoms to oxygen atoms in the cyclic compound is 2 or less.
[0067] The present disclosure provides a method for preparing titanium silicon molecular sieve, by introducing a cyclic compound selected from a group having a C number of less than or equal to 6 and a ratio of the C number of atoms to the O number of atoms of less than or equal to 2 as an auxiliary agent to participate in the preparation of the titanium silicon molecular sieve, it is helpful to produce an improved hydrogen environment in the internal pores of the molecular sieve, which is conducive to allowing both oily and aqueous raw materials to efficiently diffuse close to the active center to participate in the reaction. The preparation method of the titanium silicon molecular sieve provided by the present disclosure is simple, easy to implement, and low in cost.
[0068] In one embodiment, in step S1, the molar ratio of silicon source: titanium source: first template: water is 1: (0.001-0.10): (0.05-0.30): (10-40), preferably 1: (0.01-0.04): (0.10-0.25): (15-30), preferably 1: (0.015-0.03): (0.15-0.20): (18-25); wherein the silicon source is calculated as SiO2, and the titanium source is calculated as TiO2. The titanium silicon molecular sieve is prepared according to the optimized molar ratio in this embodiment, which can further improve the catalytic performance of the titanium silicon molecular sieve.
[0069] In a specific embodiment, the first template and the second template are each independently selected from one or more compounds having the structure described in the following formula (M-1):
[0070] wherein R1, R2, R3 and R4 are each independently selected from an alkyl group having 2 to 4 carbon atoms and an alkenyl group having 2 to 4 carbon atoms;
[0071] Preferably, in formula (M-1), R1, R2, R3 and R4 are each independently selected from an alkyl group having 3 carbon atoms or an alkenyl group having 3 carbon atoms;
[0072] Further preferably, the first template and the second template are each independently selected from one or more of tetrapropylammonium hydroxide, allyltripropylammonium hydroxide, acryltripropylammonium hydroxide, diallyldipropylammonium hydroxide, diallyldipropylammonium hydroxide, allylpropenyldipropylammonium hydroxide, diallylpropenylpropylammonium hydroxide, diallylallylpropylammonium hydroxide, triallylpropylammonium hydroxide, tripropenylpropylammonium hydroxide, tetraallylammonium hydroxide and tetraallylammonium hydroxide; preferably one or more selected from tetrapropylammonium hydroxide, allyltripropylammonium hydroxide, acryltripropylammonium hydroxide, allylpropenyldipropylammonium hydroxide, triallylpropylammonium hydroxide and tetraallylammonium hydroxide; further preferably one or more selected from tetrapropylammonium hydroxide, allyltripropylammonium hydroxide and acryltripropylammonium hydroxide.
[0073] In a specific embodiment, the silicon source is selected from at least one of organic silicon ester, solid silica gel, white carbon black and silica sol; preferably, it is selected from at least one of organic silicon ester; preferably, the SiO2 content in the solid silicon source (solid silica gel, white carbon black and silica sol) is not less than 99.99% by weight based on dry weight, and the total mass content of Fe, Al and Na impurities is less than 10ppm; for example, the SiO2 content is 99.99-100% by weight, usually greater than 99.99 and less than 100% by weight. The solid silicon source can be high-purity silica gel and / or white carbon black, preferably white carbon black; wherein the SiO2 content in the high-purity silica gel is preferably greater than or equal to 99.99% by weight, for example, greater than 99.99% by weight and less than 100% by weight, and the total mass content of Fe, Al and Na impurities is less than 10ppm. Based on the dry weight of the white carbon black, the SiO2 content in the white carbon black is preferably 99.99 wt% or more, for example, 99.99 to 100 wt%, for example, greater than 99.99 wt% and less than 100 wt%, and the total mass content of Fe, Al and Na impurities in the white carbon black is less than 10 ppm in terms of atoms. The specific surface area of the white carbon black is between 20 and 1000 m 2 / g, preferably 50 to 400 m 2 / g.
[0074] In a preferred embodiment, the organic silicon ester is selected from one or more compounds having the structure shown in the following formula (M-2):
[0075]
[0076] Among them, R a , R b , R c and R d Each is independently selected from an alkyl group having 1 to 4 carbon atoms, wherein the alkyl group is a branched or straight chain alkyl group; preferably, the R a , R b , R c and R d Each is independently selected from methyl, ethyl, n-propyl, isopropyl, n-butyl, sec-butyl, isobutyl or tert-butyl; further preferably, the organosilicon ester is selected from one or more of tetramethyl silicate, tetraethyl silicate, tetrabutyl silicate and dimethyl diethyl silicate; further preferably, it is selected from one or more of tetramethyl silicate, tetraethyl silicate and dimethyl diethyl silicate.
[0077] In one embodiment, the titanium source is selected from one or more of an organic titanium source and an inorganic titanium source;
[0078] Preferably, the organic titanium source is a titanium-containing organic acid ester, and the titanium-containing organic acid ester is selected from one or more compounds having a structure represented by the following formula (M-3):
[0079]
[0080] Among them, R e , R f , R g and R h are each selected from an alkyl group having 1 to 6 carbon atoms, preferably a straight-chain alkyl group having 1 to 4 carbon atoms and a branched-chain alkyl group having 3 to 6 carbon atoms, and more preferably R e , R f , R g and R h are independently selected from a straight chain alkyl group having 2 to 4 carbon atoms and a branched chain alkyl group having 2 to 4 carbon atoms; optionally, R e , R f , R g and R hEach of the following groups is independently selected from one of methyl, ethyl, n-propyl, isopropyl, n-butyl, sec-butyl, isobutyl, tert-butyl, isopentyl, hexyl and isohexyl; preferably each of the following groups is independently selected from one of ethyl, n-propyl, isopropyl, n-butyl, sec-butyl, isobutyl and tert-butyl;
[0081] Preferably, the inorganic titanium source is selected from one or more of titanium tetrachloride, titanium trichloride, titanyl sulfate, titanocene dichloride, fluorotitanic acid and ammonium fluorotitanate;
[0082] Further preferably, the titanium source is selected from one or more of tetraethyl titanate, tetrapropyl titanate and tetrabutyl titanate.
[0083] In one embodiment, in step S1, the conditions of the first hydrothermal treatment include: the hydrothermal temperature is 150°C to 200°C, the hydrothermal time is 2h to 100h, and the hydrothermal crystallization pressure is the autogenous pressure; preferably, the hydrothermal temperature is 160°C to 190°C, and the hydrothermal crystallization time is 4h to 80h; further preferably, the hydrothermal temperature is 165°C to 188°C, and the hydrothermal crystallization time is 5h to 40h;
[0084] Optionally, before the first hydrothermal treatment, the method further comprises: performing a hydrolysis-to-alcohol removal treatment on a raw material mixture obtained by mixing the silicon source, the titanium source, the first template and water; Optionally, the conditions of the hydrolysis-to-alcohol removal treatment include: treating at 5°C to 120°C for 0.5h to 48h; preferably treating at 50°C to 100°C for 1h to 24h;
[0085] Optionally, the conditions of the first calcination treatment include: a calcination temperature of 300°C to 800°C, a calcination time of 0.5h to 24h; preferably, a calcination temperature of 400°C to 600°C, a calcination time of 2h to 12h; a calcination atmosphere of one of air, oxygen-enriched air and oxygen-depleted air. In the present disclosure, oxygen-enriched air refers to air with an oxygen concentration of 22% by volume or more; oxygen-depleted air refers to air with an oxygen concentration of 20% by volume or less.
[0086] In one embodiment, in step S2, the weight ratio of the molecular sieve intermediate product: the second template: the auxiliary agent: water is 1: (0.05-0.50): (0.0001-0.005): (1-10), preferably 1: (0.15-0.45): (0.0005-0.002): (2-6). The titanium silicon molecular sieve is prepared according to the optimized weight ratio in this embodiment, which can further improve the catalytic performance of the titanium silicon molecular sieve.
[0087] In one embodiment, in step S2, the auxiliary agent is selected from one or more of trioxymethylene (C3H6O3, the ratio of the number of carbon atoms to oxygen atoms is 1), tetraoxymethylene (C4H8O4, the ratio of the number of carbon atoms to oxygen atoms is 1), 1,3-dioxolane (C3H6O2, the ratio of the number of carbon atoms to oxygen atoms is 1.5), 1,4-dioxane (C4H8O2, the ratio of the number of carbon atoms to oxygen atoms is 2), glycerol formal (C4H8O3, the ratio of the number of carbon atoms to oxygen atoms is 1.33) and propylene glycol formal (C4H8O2, the ratio of the number of carbon atoms to oxygen atoms is 2); preferably, it is selected from one or more of trioxymethylene, tetraoxymethylene, 1,3-dioxolane, 1,4-dioxane and glycerol formal; more preferably, it is selected from one or more of trioxymethylene, 1,3-dioxolane and glycerol formal.
[0088] In one embodiment, in step S2, the conditions of the second hydrothermal treatment include: temperature of 150°C to 200°C, time of 2h to 72h, and pressure of autogenous pressure; preferably, temperature of 160°C to 180°C, time of 12h to 48h;
[0089] Optionally, the conditions of the second calcination treatment include: a calcination temperature of 350°C to 800°C, and a calcination time of 0.5h to 24h; preferably, a calcination temperature of 450°C to 600°C, and a calcination time of 1h to 8h; and a calcination atmosphere of one of air, oxygen-enriched air and oxygen-deficient air.
[0090] In a specific embodiment, in steps S1 and S2, the specific operations of the first solid-liquid separation and the second solid-liquid separation may include methods such as sedimentation, centrifugation, filtration, and evaporation; and after the solid-liquid separation and before the roasting treatment, the solid product obtained by the solid-liquid separation may also be washed and dried; wherein the washing may be flushing the molecular sieve with water or an organic solvent to achieve a pH value of the flushing liquid of less than 9; the drying may remove most of the water in the molecular sieve to reduce the amount of water evaporation during roasting, and the drying temperature may be 100°C to 200°C, and the time may be 0.5h to 24h.
[0091] A third aspect of the present disclosure provides a titanium silicon molecular sieve prepared according to the method described in the second aspect of the present disclosure.
[0092] The fourth aspect of the present disclosure provides the use of the titanium silicon molecular sieve described in the first aspect or the third aspect of the present disclosure in catalyzing organic reactions.
[0093] In the present disclosure, the organic matter reactions include: catalytic oxidation reaction (olefin oxidation / epoxidation to prepare aldehydes, ketones, acids, epoxy compounds, and vicinal diols; alkane oxidation to prepare alcohols, aldehydes, and acids; alcohol oxidation to prepare ketones and acids; aldehyde oxidation to prepare acids; aromatic hydrocarbon oxidation to prepare phenols; sulfide oxidation to prepare sulfoxides and sulfones), reduction reaction, oximation reaction (aldehyde / ketone ammoximation to prepare amides and lactams), aldol condensation reaction, substitution / halogenation reaction, elimination reaction, ester exchange reaction, dehydration reaction, etherification reaction, esterification reaction, double bond / triple bond addition reaction, diene addition reaction, Beckmann rearrangement reaction (cyclohexanone oxime gas phase rearrangement to prepare caprolactam), hydrogen transfer reaction, etc.
[0094] In a preferred embodiment, the catalytic organic reaction includes a reaction of preparing propylene oxide by epoxidation of propylene; optionally, the reaction includes the following steps:
[0095] Under epoxidation reaction conditions, propylene, hydrogen peroxide, methanol and a catalyst are contacted to carry out an oxidation reaction; the catalyst comprises the titanium silicon molecular sieve;
[0096] Preferably, the epoxidation reaction conditions include: a molar ratio of propylene to hydrogen peroxide of 1.0 to 5.0:1, a molar ratio of methanol to hydrogen peroxide of 0 to 10:1, and a weight hourly space velocity of hydrogen peroxide of 0.01 h / min when a fixed bed is used as a reactor. -1 ~3h -1 ; The reaction temperature is 20℃~80℃.
[0097] In the application of the titanium silicalite provided in the present disclosure, the titanium silicalite or the catalyst containing the titanium silicalite can be used in the form of powder or shaped spheres, strips, cakes, granules, etc., and can be mixed with other catalysts; the application can be carried out in a variety of reactors such as kettle reactors, slurry bed reactors, fixed bed reactors, fluidized bed reactors, moving bed reactors, microchannel reactors, etc.; the reaction raw materials and catalysts can be fed all at once, intermittently, or continuously.
[0098] It will be understood by those skilled in the art that the separation of the product and the catalyst can be achieved in a variety of ways. For example, when the original powdered molecular sieve is used as the catalyst, the product separation and the catalyst recovery and reuse can be achieved by sedimentation, filtration, centrifugation, evaporation, membrane separation, etc. Alternatively, the catalyst can be formed and loaded into a fixed bed reactor, and the catalyst can be recovered after the reaction is completed. The separation and recovery methods of various catalysts can be known methods.
[0099] The present disclosure is further described in detail below through examples. The raw materials used in the examples can all be obtained through commercial channels.
[0100] In the following embodiments and comparative examples:
[0101] The structure of the molecular sieve was determined by XRD analysis, and the test instrument was Siemens D5005 X-ray diffractometer; the test method included: Cu target, Kα radiation, Ni filter, tube point voltage 40kV, tube current 250mA, scintillation counter, step width 0.02°. Scanning range 2θ = 5° to 35°, scanning rate 0.4 (°) / min.
[0102] The chemical composition of the molecular sieve was analyzed and determined using a Rigaku 3721E fluorescence spectrometer.
[0103] 1 H MAS NMR was performed on a Bruker AVANCE 600 MHz NMR instrument with a rotor speed of 12 kHz, a cycle delay of 2 s, and 256 samples.
[0104] Unless otherwise specified, the raw materials used in the examples are all chemically pure reagents. The reagents used in the present disclosure can be purchased through common commercial channels or prepared by known methods.
[0105] In the following examples and comparative examples, the relative crystallinity of the molecular sieves is based on the crystallinity of the all-silicon molecular sieve prepared in Comparative Example 1.
[0106] Comparative Example 1
[0107] In this comparative example, MFI type all-silicon molecular sieve S-1 was synthesized.
[0108] According to the molar ratio of silicon source (in terms of SiO2): first template: water of 1:0.2:25, tetraethyl silicate, tetrapropylammonium hydroxide (25 wt%) solution and deionized water were mixed, stirred at 30°C for about 2 hours, and then stirred at 60°C for about 6 hours to obtain a sol. The obtained sol was treated at 170°C for 72 hours, and then the obtained slurry was filtered, washed with deionized water until the pH of the filtrate was lower than 9, dried at 120°C for 6 hours, and calcined at 550°C for 6 hours to obtain the S-1 product. S-1 was tested by XRD, and it had an MFI-type skeleton structure, and the relative crystallinity was recorded as 100%.
[0109] Comparative Example 2
[0110] In this comparative example, conventional MFI type titanium silicalite TS-1 was synthesized.
[0111] According to the molar ratio of silicon source (in terms of SiO2): titanium source (in terms of TiO2): first template: water of 1:0.02:0.2:25, tetraethyl silicate, tetrabutyl titanate, tetrapropylammonium hydroxide (25 wt%) solution and deionized water were mixed, stirred at 30°C for about 2 hours, and then stirred at 60°C for about 6 hours to obtain a sol. The obtained sol was treated at 170°C for 72 hours, and then the obtained slurry was filtered, washed with deionized water until the pH of the filtrate was less than 9, dried at 120°C for 6 hours, and calcined at 550°C for 6 hours to obtain the TS-1 product. TS-1 was subjected to XRD testing, which showed that it had an MFI-type skeleton structure with a relative crystallinity of 85%. The chemical composition of TS-1 was analyzed by XRF, and it was found that the molar ratio of silicon and titanium elements was 1:0.02. TS-1 was subjected to 1 HMAS NMR test revealed that it had resonance absorption peaks at 1.96 ppm and 1.68 ppm, but no resonance absorption peak at 1.13 ppm.
[0112] Comparative Example 3
[0113] In this comparative example, conventional MFI type titanium silicalite HTS is synthesized (refer to the method of Chinese patent CN1260241A).
[0114] According to the molar ratio of silicon source (in terms of SiO2): titanium source (in terms of TiO2): first template: water of 1:0.02:0.2:25, tetraethyl silicate, tetrabutyl titanate, tetrapropylammonium hydroxide (25 wt%) solution and deionized water were mixed, stirred at 30°C for about 2 hours, and then stirred at 60°C for about 6 hours to obtain a sol. The obtained sol was treated at 170°C for 72 hours, and then the obtained slurry was filtered, washed with deionized water until the pH of the filtrate was lower than 9, dried at 120°C for 6 hours, and calcined at 550°C for 6 hours to obtain the intermediate TS-1 product. The intermediate TS-1 was then mixed with the second template tetrapropylammonium hydroxide (25 wt%) and water in a weight ratio of 1:0.2:6, and then treated at 170°C for 24 hours, and then the obtained slurry was filtered, dried, and calcined according to the above method to obtain the product HTS. XRD test of HTS showed that it had an MFI skeleton structure with a relative crystallinity of 95%. XRF analysis of the chemical composition of HTS showed that the molar ratio of silicon to titanium was 1:0.021. 1 H MAS NMR test revealed that it had resonance absorption peaks at 1.96 ppm and 1.68 ppm, but no resonance absorption peak at 1.13 ppm.
[0115] Example 1
[0116] In this example, MFI type titanium silicalite TS-1-A was synthesized.
[0117] According to the molar ratio of silicon source (in terms of SiO2): titanium source (in terms of TiO2): first template: water of 1:0.02:0.2:25, tetraethyl silicate, tetrabutyl titanate, tetrapropylammonium hydroxide (25 wt%) solution and deionized water were mixed, stirred at 30°C for about 2 hours, and then stirred at 60°C for about 6 hours to obtain a sol. The obtained sol was hydrothermally treated at 170°C for 72 hours, and then the obtained slurry was filtered, washed with deionized water until the pH of the filtrate was less than 9, dried at 120°C for 6 hours, and calcined at 550°C for 6 hours to obtain an intermediate TS-1 product. The intermediate TS-1 is then mixed with the second template tetrapropylammonium hydroxide (25 wt%), the auxiliary trioxymethylene and water in a weight ratio of 1:0.2:0.001:6, and then treated at 170°C for 24 hours. The resulting slurry is then filtered, dried and calcined according to the method and conditions described above in this embodiment to obtain the product TS-1-A.
[0118] XRD test was performed on TS-1-A. Figure 6 As shown in the figure, there is a peak at 2θ of 22° to 25°, indicating that it has an MFI-type skeleton structure and a relative crystallinity of 94%. XRF analysis of the chemical composition of TS-1-A revealed that its silicon-titanium molar ratio was 1:0.021. 1 HMAS NMR test found that it has resonance absorption peaks at 1.96ppm, 1.68ppm, 1.13ppm and 0.7ppm, among which I 1.68 / I 1.13 ,I 1.96 / I 1.68 and I 0.7 / I 1.13 The values are listed in Table 1.
[0119] Example 2
[0120] In this example, MFI type titanium silicalite TS-1-B is synthesized.
[0121] According to the molar ratio of silicon source (in terms of SiO2): titanium source (in terms of TiO2): first template: water of 1:0.03:0.15:18, tetraethyl silicate, tetrabutyl titanate, tetrapropylammonium hydroxide (25 wt%) solution and deionized water were mixed, stirred at 30°C for about 2 hours, and then stirred at 80°C for about 6 hours to obtain a sol. The obtained sol was treated at 170°C for 80 hours, and then the obtained slurry was filtered, washed with deionized water until the pH of the filtrate was less than 9, dried at 120°C for 8 hours, and calcined at 550°C for 12 hours to obtain an intermediate TS-1 product. The intermediate TS-1 was then mixed with the second template tetrapropylammonium hydroxide (25 wt%), the auxiliary agent 1,3-epoxypentane and water in a weight ratio of 1:0.15:0.0005:2, and then treated at 170°C for 24 hours. The resulting slurry was filtered, dried and calcined according to the aforementioned method and conditions in this embodiment to obtain the product TS-1-B.
[0122] XRD test of TS-1-B showed that it had an MFI skeleton structure with a relative crystallinity of 94%. XRF analysis of the chemical composition of TS-1-B showed that its molar ratio of silicon to titanium was 1:0.031. 1 H MAS NMR test revealed that it had resonance absorption peaks at 1.96 ppm, 1.68 ppm, 1.13 ppm and 0.7 ppm, among which I 1.68 / I 1.13 ,I 1.96 / I 1.68 and I 0.7 / I 1.13 The values are listed in Table 1.
[0123] Example 3
[0124] In this example, MFI type titanium silicalite molecular sieve TS-1-C is synthesized.
[0125] According to the molar ratio of silicon source (in terms of SiO2): titanium source (in terms of TiO2): first template: water of 1:0.015:0.2:18, tetraethyl silicate, tetrabutyl titanate, tetrapropylammonium hydroxide (25 wt%) solution and deionized water were mixed, stirred at 30°C for about 2 hours, and then stirred at 90°C for about 4 hours to obtain a sol. The obtained sol was treated at 170°C for 60 hours, and then the obtained slurry was filtered, washed with deionized water until the pH of the filtrate was less than 9, dried at 120°C for 8 hours, and calcined at 550°C for 4 hours to obtain an intermediate TS-1 product. The intermediate TS-1 is then mixed with the second template agent allyl tripropyl ammonium hydroxide (25 wt%), the auxiliary agent glycerol formal and water in a weight ratio of 1:0.15:0.001:3, and then treated at 170°C for 48 hours. The resulting slurry is then filtered, dried and calcined according to the aforementioned method and conditions in this embodiment to obtain the product TS-1-C.
[0126] XRD test of TS-1-C showed that it had an MFI skeleton structure with a relative crystallinity of 95%. XRF analysis of the chemical composition of TS-1-C showed that its molar ratio of silicon to titanium was 1:0.015. 1 H MAS NMR test revealed that it had resonance absorption peaks at 1.96 ppm, 1.68 ppm, 1.13 ppm and 0.7 ppm, among which I 1.68 / I 1.13 ,I 1.96 / I 1.68 and I 0.7 / I 1.13 The values are listed in Table 1.
[0127] Example 4
[0128] In this example, MFI type titanium silicalite TS-1-D was synthesized.
[0129] According to the molar ratio of silicon source (in terms of SiO2): titanium source (in terms of TiO2): first template: water of 1:0.03:0.2:20, tetraethyl silicate, tetraethyl titanate, allyl tripropyl ammonium hydroxide (25 wt%) solution and deionized water were mixed, stirred at 30°C for about 2 hours, and then stirred at 80°C for about 4 hours to obtain a sol. The obtained sol was treated at 170°C for 48 hours, and then the obtained slurry was filtered, washed with deionized water until the pH of the filtrate was less than 9, dried at 120°C for 6 hours, and calcined at 500°C for 4 hours to obtain an intermediate TS-1 product. The intermediate TS-1 was then mixed with the second template tetrapropylammonium hydroxide (25 wt%), the auxiliary agent 1,3-epoxypentane and water in a weight ratio of 1:0.3:0.002:5, and then treated at 170°C for 24 hours. The resulting slurry was filtered, dried and calcined according to the aforementioned method and conditions in this embodiment to obtain the product TS-1-D.
[0130] XRD test of TS-1-D showed that it had an MFI skeleton structure with a relative crystallinity of 95%. XRF analysis of the chemical composition of TS-1-D showed that the molar ratio of silicon to titanium was 1:0.032. 1 H MAS NMR test revealed that it had resonance absorption peaks at 1.96 ppm, 1.68 ppm, 1.13 ppm and 0.7 ppm, among which I 1.68 / I 1.13 ,I 1.96 / I 1.68 and I 0.7 / I 1.13 The values are listed in Table 1.
[0131] Example 5
[0132] In this example, MFI type titanium silicalite TS-1-E is synthesized.
[0133] According to the molar ratio of silicon source (in terms of SiO2): titanium source (in terms of TiO2): first template: water of 1:0.02:0.15:25, tetraethyl silicate, tetraethyl titanate, propylene tripropyl ammonium hydroxide (25 wt%) solution and deionized water were mixed, stirred at 30°C for about 2 hours, and then stirred at 90°C for about 8 hours to obtain a sol. The obtained sol was treated at 170°C for 12 hours, and then the obtained slurry was filtered, washed with deionized water until the pH of the filtrate was less than 9, dried at 120°C for 12 hours, and calcined at 500°C for 6 hours to obtain an intermediate TS-1 product. The intermediate TS-1 is then mixed with the second template acryltripropylammonium hydroxide (25 wt%), the auxiliary agent glycerol formal and water in a weight ratio of 1:0.45:0.001:4, and then treated at 170°C for 12 hours. The resulting slurry is then filtered, dried and calcined according to the aforementioned method and conditions in this embodiment to obtain the product TS-1-E.
[0134] XRD test of TS-1-E showed that it had an MFI skeleton structure with a relative crystallinity of 96%. XRF analysis of the chemical composition of TS-1-E showed that its silicon-titanium molar ratio was 1:0.021. 1 H MAS NMR test revealed that it had resonance absorption peaks at 1.96 ppm, 1.68 ppm, and 1.13 ppm, among which I 1.68 / I 1.13 ,I 1.96 / I 1.68 The values are listed in Table 1.
[0135] Example 6
[0136] In this example, MFI type titanium silicalite TS-1-F is synthesized.
[0137] According to the molar ratio of silicon source (in terms of SiO2): titanium source (in terms of TiO2): first template: water of 1:0.025:0.2:18, tetraethyl silicate, tetraethyl titanate, allyl tripropyl ammonium hydroxide (25 wt%) solution and deionized water were mixed, stirred at 30°C for about 2 hours, and then stirred at 90°C for about 12 hours to obtain a sol. The obtained sol was treated at 170°C for 24 hours, and then the obtained slurry was filtered, washed with deionized water until the pH of the filtrate was less than 9, dried at 120°C for 12 hours, and calcined at 500°C for 6 hours to obtain an intermediate TS-1 product. The intermediate TS-1 is then mixed with the second template agent allyl tripropyl ammonium hydroxide (25 wt%), the auxiliary agent glycerol formal and water in a weight ratio of 1:0.3:0.0015:6, and then treated at 170°C for 12 hours. The resulting slurry is then filtered, dried and calcined according to the aforementioned method and conditions in this embodiment to obtain the product TS-1-F.
[0138] XRD test of TS-1-F showed that it had an MFI skeleton structure with a relative crystallinity of 95%. XRF analysis of the chemical composition of TS-1-F showed that its molar ratio of silicon to titanium was 1:0.026. 1 H MAS NMR test revealed that it had resonance absorption peaks at 1.96 ppm, 1.68 ppm, and 1.13 ppm, among which I 1.68 / I 1.13 ,I 1.96 / I 1.68 The values are listed in Table 1.
[0139] Example 7
[0140] This example refers to the preparation method in Example 1, and the difference from Example 1 is that:
[0141] Tetraethyl silicate, tetrabutyl titanate, tetrapropylammonium hydroxide (25 wt%) solution and deionized water were mixed according to the molar ratio of silicon source (in terms of SiO2): titanium source (in terms of TiO2): first template: water of 1:0.04:0.1:30. The rest of the process was the same as in Example 1, and the product TS-1-G was finally prepared.
[0142] XRD test of TS-1-G showed that it had an MFI skeleton structure with a relative crystallinity of 94%. XRF analysis of the chemical composition of TS-1-G showed that its silicon-titanium molar ratio was 1:0.042. 1 H MAS NMR test revealed that it had resonance absorption peaks at 1.96 ppm, 1.68 ppm, 1.13 ppm and 0.7 ppm, among which I 1.68 / I1.13 ,I 1.96 / I 1.68 and I 0.7 / I 1.13 The values are listed in Table 1.
[0143] Example 8
[0144] This example refers to the preparation method in Example 1, and the difference from Example 1 is that:
[0145] According to the molar ratio of silicon source (in terms of SiO2): titanium source (in terms of TiO2): first template: water of 1:0.1:0.05:40, tetraethyl silicate, tetrabutyl titanate, tetrapropylammonium hydroxide (25 wt%) solution and deionized water are mixed; and the intermediate is mixed with the second template tetrapropylammonium hydroxide (25 wt%), the auxiliary agent trioxymethylene and water in a weight ratio of 1:0.05:0.0001:10, and the remaining process is the same as in Example 1, and finally the product TS-1-H is prepared.
[0146] XRD test of TS-1-H showed that it had an MFI skeleton structure with a relative crystallinity of 93%. XRF analysis of the chemical composition of TS-1-H showed that its silicon-titanium molar ratio was 1:0.11. 1 H MAS NMR test revealed that it had resonance absorption peaks at 1.96 ppm, 1.68 ppm, 1.13 ppm and 0.7 ppm, among which I 1.68 / I 1.13 ,I 1.96 / I 1.68 and I 0.7 / I 1.13 The values are listed in Table 1.
[0147] Comparison example
[0148] This example refers to the preparation method in Example 1, and the difference from Example 1 is that:
[0149] Tetraethyl silicate, tetrabutyl titanate, tetrapropylammonium hydroxide (25 wt%) solution and deionized water were mixed according to the molar ratio of silicon source (in terms of SiO2): titanium source (in terms of TiO2): first template: water of 1:0.15:0.5:50; and the intermediate was mixed with the second template tetrapropylammonium hydroxide (25 wt%), the auxiliary agent trioxymethylene and water in a weight ratio of 1:0.02:0.008:15. The remaining process was the same as in Example 1, and the product TS-1-I was finally prepared.
[0150] XRD test of TS-1-I showed that it had an MFI skeleton structure with a relative crystallinity of 92%. XRF analysis of the chemical composition of TS-1-I showed that its molar ratio of silicon to titanium was 1:0.16. 1 H MAS NMR test revealed that it had resonance absorption peaks at 1.96 ppm, 1.68 ppm, 1.13 ppm and 0.7 ppm, among which I 1.68 / I 1.13 ,I 1.96 / I 1.68 and I 0.7 / I 1.13 The values are listed in Table 1.
[0151] Example 9
[0152] This example refers to the preparation method in Example 1, and the difference from Example 1 is that:
[0153] A mixture of tetraethyl silicate, tetrabutyl titanate, tetrapropylammonium hydroxide solution and deionized water is stirred at 30°C for about 2 hours, and then stirred at 60°C for about 6 hours to obtain a sol. The obtained sol is hydrothermally treated at 150°C for 100 hours; then the obtained slurry is filtered, washed with deionized water until the pH of the filtrate is lower than 9, dried at 120°C for 6 hours, and calcined at 800°C for 0.5 hours to obtain an intermediate product. The intermediate is then treated with a mixture of the second template tetrapropylammonium hydroxide, the auxiliary agent trioxymethylene and water at 150°C for 2 hours, and the obtained slurry is filtered, dried and calcined according to the aforementioned method and conditions in this embodiment to obtain products TS-1-J, I 1.68 / I 1.13 ,I 1.96 / I 1.68 and I 0.7 / I 1.13 The values are listed in Table 1.
[0154] Example 10
[0155] This example refers to the preparation method in Example 1, and the difference from Example 1 is that:
[0156] A mixture of tetraethyl silicate, tetrabutyl titanate, tetrapropylammonium hydroxide solution and deionized water is stirred at 30°C for about 2 hours, and then stirred at 60°C for about 6 hours to obtain a sol. The obtained sol is hydrothermally treated at 220°C for 1 hour; then the obtained slurry is filtered, washed with deionized water until the pH of the filtrate is lower than 9, dried at 120°C for 6 hours, and calcined at 340°C for 30 hours to obtain an intermediate product. The intermediate is then treated with a mixture of the second template tetrapropylammonium hydroxide, the auxiliary agent trioxymethylene and water at 220°C for 1 hour, and the obtained slurry is filtered, dried and calcined according to the aforementioned method and conditions in this embodiment to obtain the product TS-1-K, wherein I 1.68 / I 1.13 ,I 1.96 / I 1.68 The values are listed in Table 1.
[0157] The silicon-titanium molar ratio, I 1.68 / I 1.13 ,I 1.96 / I 1.68 ,I 0.7 / I 1.13 The relative crystallinity and other data are listed in Table 1 below.
[0158] Table 1
[0159]
[0160] The symbol “-” indicates that the value does not exist. Taking the titanium silicon molecular sieve prepared in Example 1 as an example, the titanium silicon molecular sieve 1 The peak intensity I of the signal peak at 1.68±0.15 ppm in the H MAS NMR spectrum 1.68 The peak intensity of the signal peak at the position of 2119, 1.13±0.15ppm is I 1.13 The peak intensity of the signal peak at the position of 498, 1.96±0.15ppm is I 1.96 The peak intensity of the signal peak at the position of 2733, 0.7±0.15ppm is I 0.7 is 351.
[0161] Evaluation test case
[0162] This test example is used to evaluate the performance of the titanium silicon molecular sieve prepared in the comparative example and the example as a catalyst in catalyzing the propylene epoxidation reaction. Specifically, it includes the following process:
[0163] Propylene epoxidation reaction evaluation was carried out in a fixed bed reactor. The catalyst loading was 5 mL, and the feed was divided into two routes, a propylene route and a methanol hydrogen peroxide mixture route. The two pipelines were transported to the inlet of the reaction tube through a feed pump for mixing, and then entered the catalyst bed for reaction. The raw materials were fed in from the bottom and discharged from the top. The specific reaction conditions are listed in Table 2 below. The timing reaction started from the time the raw materials entered the reactor, and sampling and analysis were performed at regular intervals to obtain the product and determine the composition. The data when the reaction first reached stability were compared. The first stability refers to when the reaction is started, the hydrogen peroxide conversion rate and propylene oxide selectivity at a certain moment are less than 1% different from the data 24 hours before and after the moment. The inspection indicators are as follows, and the test conditions and evaluation results are listed in Table 2 below.
[0164] Hydrogen peroxide conversion rate (%) = (moles of hydrogen peroxide in the raw material - moles of hydrogen peroxide in the product) / moles of hydrogen peroxide in the raw material × 100%;
[0165] Propylene oxide selectivity (%) = the number of moles of propylene oxide produced in the product / the number of moles of all products produced × 100%;
[0166] The conversion rate of hydrogen peroxide was measured by sodium thiosulfate titration, and the selectivity of propylene oxide was measured by gas chromatography, wherein the chromatographic analysis conditions were: Agilent-6890 chromatograph, HP-5 capillary column, injection volume 0.5 μL, injection port temperature 280°C. The column temperature was maintained at 100°C for 2 min, then increased to 250°C at a rate of 15°C / min and maintained for 10 min. FID detector, detector temperature 300°C.
[0167] Table 2
[0168]
[0169] From the data in Table 2 above, we can see that:
[0170] In test examples 1 and 3, the titanium silicalite prepared in comparative example 2 and the comparative example is used as a catalyst. Under the condition of low methanol dosage (the molar ratio of methanol to hydrogen peroxide is 4:1), when the reaction reaches the initial stability, the hydrogen peroxide conversion rate is only 62% and 75%, and the propylene oxide selectivity is only 94% and 93%, which is significantly lower than the hydrogen peroxide conversion rate and propylene oxide selectivity that can be achieved under the condition of low methanol dosage when the titanium silicalite prepared by the embodiment of the present disclosure is used as a catalyst in test examples 5 to 10. It shows that the titanium silicalite provided by the present disclosure can be applied to the reaction in which oil phase and water phase materials exist at the same time, which is conducive to the diffusion of reactant molecules close to the active center, thereby reducing the amount of solvent, reducing energy consumption and material consumption, and reducing the cost of catalytic reaction;
[0171] By comparing test examples 2 and 3, it can be seen that under the premise of using the titanium silicon molecular sieve obtained in comparative example 3 as a catalyst, when the amount of methanol solvent is reduced (the molar ratio of methanol to hydrogen peroxide is reduced from 8:1 to 4:1), the reduction rate of hydrogen peroxide conversion is 24.2%, and the reduction rate of propylene oxide selectivity is 6.45%; by comparing test examples 4 and 5, it can be seen that under the premise of using the titanium silicon molecular sieve obtained in Example 1 as a catalyst, when the amount of methanol solvent is reduced (the molar ratio of methanol to hydrogen peroxide is reduced from 8:1 to 4:1), the reduction rate of hydrogen peroxide conversion is 8.1%, and the reduction rate of propylene oxide selectivity is 1%, which is much lower than the reduction rate of hydrogen peroxide conversion and propylene oxide selectivity of the titanium silicon molecular sieve obtained in comparative example 3, indicating that the titanium silicon molecular sieve provided by the present disclosure can also have a good catalytic effect under low methanol solvent conditions;
[0172] By comparing test examples 10 and 11, it can be seen that under the premise of using the titanium silicon molecular sieve obtained in Example 6 as a catalyst, when the amount of methanol solvent is reduced (the molar ratio of methanol to hydrogen peroxide is reduced from 4:1 to 0:1), the hydrogen peroxide conversion rate in test example 11 can still reach 90%, and the propylene oxide selectivity can still reach 97%, indicating that the titanium silicon molecular sieve provided by the present disclosure can still have a good catalytic effect without adding methanol solvent;
[0173] According to the data in Table 1, it can be seen that the titanium silicon molecular sieves prepared in Examples 3 to 6 have a high 1.68 / I 1.13 The value of is within the optimized range of "2.5 to 4.0". Test Examples 7 to 10 use the titanium silicon molecular sieve prepared in Examples 3 to 6 as a catalyst. Compared with Test Examples 5 to 6 using the titanium silicon molecular sieve prepared in Examples 1 to 2 as a catalyst, under the same reaction conditions, the hydrogen peroxide conversion rate and propylene oxide selectivity of Test Examples 7 to 10 are higher;
[0174] By comparing Test Example 5 with Test Example 12, the catalyst used in Test Example 1 (the titanium silicon molecular sieve prepared in Example 1) has a raw material molar ratio in the preparation process within the preferred range provided in the present disclosure, and Test Example 5 can obtain a higher hydrogen peroxide conversion rate compared with Test Example 12 (the titanium silicon molecular sieve prepared in Example 7); further, by comparing Test Example 12 with Test Example 13, the titanium silicon molecular sieve used in Test Example 12 has a molar ratio of 1:1. 1.68 / I 1.13 The value of is within the optimized range of "2.0 to 4.5", and Test Example 12 can obtain a higher hydrogen peroxide conversion rate and propylene oxide selectivity; further, by comparing Test Example 13 with Test Example 14, it can be seen that the titanium silicalite molecular sieve of the control example used in Test Example 14 has an I 1.68 / I 1.13The value of is not within the range of "1.5 to 6.0". Compared with Test Example 14, Test Example 13 using the titanium silicon molecular sieve prepared in Example 8 as a catalyst can obtain a higher hydrogen peroxide conversion rate and propylene oxide selectivity.
[0175] By comparing Test Example 15 and Test Example 16, it can be seen that the titanium silicalite (Example 9) used in Test Example 15 is prepared according to the reaction conditions provided in the present disclosure, and Test Example 15 has higher hydrogen peroxide conversion rate and propylene oxide selectivity than Test Example 16; further, by comparing Test Example 1 with Test Example 15, the titanium silicalite (Example 1) used in Test Example 1 is prepared according to the preferred reaction conditions provided in the present disclosure, and Test Example 1 has higher hydrogen peroxide conversion rate and propylene oxide selectivity than Test Example 15.
[0176] The preferred embodiments of the present disclosure are described in detail above; however, the present disclosure is not limited to the specific details in the above embodiments. Within the technical concept of the present disclosure, a variety of simple modifications can be made to the technical solution of the present disclosure, and these simple modifications all fall within the protection scope of the present disclosure.
[0177] It should also be noted that the various specific technical features described in the above specific embodiments can be combined in any suitable manner without contradiction. In order to avoid unnecessary repetition, the present disclosure will not further describe various possible combinations.
[0178] In addition, various embodiments of the present disclosure may be arbitrarily combined, and as long as they do not violate the concept of the present disclosure, they should also be regarded as the contents disclosed by the present disclosure.
Claims
1. A titanium silicon molecular sieve, characterized in that: The titanium silicate molecular sieve 1 In the H MAS NMR spectrum, signal peaks were present at 1.68±0.15 ppm and 1.13±0.15 ppm.
2. The titanium silicon molecular sieve according to claim 1, characterized in that: The titanium silicate molecular sieve has the following 1 H MASNMR features: The titanium silicalite molecular sieve 1 The peak intensity of the signal peak at 1.68±0.15 ppm in the H MAS NMR spectrum is recorded as I 1.68 , the titanium silicalite 1 The peak intensity of the signal peak at 1.13±0.15 ppm in the H MAS NMR spectrum is recorded as I 1.13 , the titanium silicalite molecular sieve I 1.68 / I 1.13 The value of is any value in the range of 1.5 to 6.0, more preferably any value in the range of 2.0 to 4.5, and more preferably any value in the range of 2.5 to 4.0; Optionally, the titanium silicalite molecular sieve 1 In the H MAS NMR spectrum, a signal peak is also present at the position of 1.96±0.15 ppm, and a signal peak is optionally present or absent at the position of 0.7±0.15 ppm.
3. The titanium silicon molecular sieve according to claim 1, characterized in that: The molar ratio of silicon element to titanium element in the titanium silicalite molecular sieve is preferably 1:(0.001-0.1), preferably 1:(0.008-0.05), and more preferably 1:(0.013-0.025).
4. The titanium silicon molecular sieve according to claim 1, characterized in that: The average particle size of the titanium silicate molecular sieve is 50 to 900 nm, preferably 150 to 600 nm; the BET specific surface area is 340 to 550 m 2 / g, preferably 410 to 480 m 2 / g; total pore volume is 0.14~0.7cm 3 / g, preferably 0.18 to 0.39 cm 3 / g; Optionally, the configuration of the titanium silicalite molecular sieve is selected from one or more of MFI, MEL, BEA, MWW, and SVR; preferably, the configuration of the titanium silicalite molecular sieve is MFI.
5. A method for preparing titanium silicon molecular sieve, characterized in that: The following steps are involved: S1, mixing a silicon source, a titanium source, a first template and water, and performing a first hydrothermal treatment to obtain a first slurry; performing a first solid-liquid separation treatment on the first slurry, and then performing a first roasting treatment on the obtained solid product to obtain a molecular sieve intermediate product; S2, mixing the molecular sieve intermediate product, the second template, the auxiliary agent and water, and performing a second hydrothermal treatment to obtain a second slurry; performing a second solid-liquid separation treatment on the second slurry, and then performing a second roasting treatment on the obtained solid product; The auxiliary agent is selected from cyclic compounds having 3 to 6 carbon atoms, the cyclic compound further contains oxygen atoms, and the ratio of the number of carbon atoms to oxygen atoms in the cyclic compound is 2 or less.
6. The method according to claim 5, characterized in that In step S1, the molar ratio of silicon source: titanium source: first template: water is 1: (0.001-0.10): (0.05-0.30): (10-40), preferably 1: (0.01-0.04): (0.10-0.25): (15-30), preferably 1: (0.015-0.03): (0.15-0.20): (18-25); wherein the silicon source is calculated as SiO2 and the titanium source is calculated as TiO2.
7. The method according to claim 5, characterized in that The first template and the second template are each independently selected from one or more compounds having a structure represented by the following formula (M-1): wherein R1, R2, R3 and R4 are each independently selected from an alkyl group having 2 to 4 carbon atoms and an alkenyl group having 2 to 4 carbon atoms; Preferably, in formula (M-1), R1, R2, R3 and R4 are each independently selected from an alkyl group having 3 carbon atoms or an alkenyl group having 3 carbon atoms; Further preferably, the first template and the second template are each independently selected from one or more of tetrapropylammonium hydroxide, allyltripropylammonium hydroxide, acryltripropylammonium hydroxide, diallyldipropylammonium hydroxide, diallyldipropylammonium hydroxide, allylpropenyldipropylammonium hydroxide, diallylpropenylpropylammonium hydroxide, diallylallylpropylammonium hydroxide, triallylpropylammonium hydroxide, tripropenylpropylammonium hydroxide, tetraallylammonium hydroxide and tetraallylammonium hydroxide; preferably one or more selected from tetrapropylammonium hydroxide, allyltripropylammonium hydroxide, acryltripropylammonium hydroxide, allylpropenyldipropylammonium hydroxide, triallylpropylammonium hydroxide and tetraallylammonium hydroxide; further preferably one or more selected from tetrapropylammonium hydroxide, allyltripropylammonium hydroxide and acryltripropylammonium hydroxide.
8. The method according to claim 5, characterized in that The silicon source is selected from at least one of organic silicon esters, solid silica gel, white carbon black and silica sol; preferably at least one of organic silicon esters; Optionally, the organic silicon ester is selected from one or more compounds having a structure represented by the following formula (M-2): Among them, R a , R b , R c and R d Each is independently selected from an alkyl group having 1 to 4 carbon atoms, wherein the alkyl group is a branched or straight chain alkyl group; preferably, the R a , R b , R c and R d Each is independently selected from methyl, ethyl, n-propyl, isopropyl, n-butyl, sec-butyl, isobutyl or tert-butyl; further preferably, the organosilicon ester is selected from one or more of tetramethyl silicate, tetraethyl silicate, tetrabutyl silicate and dimethyl diethyl silicate; further preferably, it is selected from one or more of tetramethyl silicate, tetraethyl silicate and dimethyl diethyl silicate; Optionally, the titanium source is selected from one or more of an organic titanium source and an inorganic titanium source; Preferably, the organic titanium source is a titanium-containing organic acid ester, and the titanium-containing organic acid ester is selected from one or more compounds having a structure represented by the following formula (M-3): Among them, R e , R f , R g and R h are each selected from an alkyl group having 1 to 6 carbon atoms, preferably a straight-chain alkyl group having 1 to 4 carbon atoms and a branched-chain alkyl group having 3 to 6 carbon atoms, and more preferably R e , R f , R g and R h are independently selected from a straight chain alkyl group having 2 to 4 carbon atoms and a branched chain alkyl group having 2 to 4 carbon atoms; optionally, R e , R f , R g and R h Each of the following groups is independently selected from one of methyl, ethyl, n-propyl, isopropyl, n-butyl, sec-butyl, isobutyl, tert-butyl, isopentyl, hexyl and isohexyl; preferably each of the following groups is independently selected from one of ethyl, n-propyl, isopropyl, n-butyl, sec-butyl, isobutyl and tert-butyl; Preferably, the inorganic titanium source is selected from one or more of titanium tetrachloride, titanium trichloride, titanyl sulfate, titanocene dichloride, fluorotitanic acid and ammonium fluorotitanate; Further preferably, the titanium source is selected from one or more of tetraethyl titanate, tetrapropyl titanate and tetrabutyl titanate.
9. The method according to claim 5, characterized in that In step S1, the conditions of the first hydrothermal treatment include: the hydrothermal temperature is 150°C to 200°C, the hydrothermal time is 2h to 100h, and the hydrothermal crystallization pressure is the autogenous pressure; preferably, the hydrothermal temperature is 160°C to 190°C, and the hydrothermal crystallization time is 4h to 80h; more preferably, the hydrothermal temperature is 165°C to 188°C, and the hydrothermal crystallization time is 5h to 40h; Optionally, before the first hydrothermal treatment, the method further comprises: performing a hydrolysis-to-alcohol removal treatment on a raw material mixture obtained by mixing the silicon source, the titanium source, the first template and water; Optionally, the conditions of the hydrolysis-to-alcohol removal treatment include: treating at 5°C to 120°C for 0.5h to 48h; preferably treating at 50°C to 100°C for 1h to 24h; Optionally, the conditions of the first calcination treatment include: a calcination temperature of 300°C to 800°C, and a calcination time of 0.5h to 24h; preferably, the calcination temperature is 400°C to 600°C, and the calcination time is 2h to 12h; and the calcination atmosphere is one of air, oxygen-enriched air and oxygen-deficient air.
10. The method according to claim 5, characterized in that In step S2, the weight ratio of the molecular sieve intermediate product: the second template: the auxiliary agent: water is 1: (0.05-0.50): (0.0001-0.005): (1-10), preferably 1: (0.15-0.45): (0.0005-0.002): (2-6).
11. The method according to claim 5, characterized in that In step S2, the auxiliary agent is selected from one or more of trioxymethylene, tetraoxymethylene, 1,3-dioxolane, 1,4-dioxane, glycerol formal and propylene glycol formal; preferably selected from one or more of trioxymethylene, tetraoxymethylene, 1,3-dioxolane, 1,4-dioxane and glycerol formal; more preferably selected from one or more of trioxymethylene, 1,3-dioxolane and glycerol formal.
12. The method according to claim 5, characterized in that In step S2, the conditions of the second hydrothermal treatment include: temperature of 150°C to 200°C, time of 2h to 72h, and pressure of autogenous pressure; preferably, temperature of 160°C to 180°C, time of 12h to 48h; Optionally, the conditions of the second calcination treatment include: a calcination temperature of 350°C to 800°C, and a calcination time of 0.5h to 24h; preferably, a calcination temperature of 450°C to 600°C, and a calcination time of 1h to 8h; and a calcination atmosphere selected from one of air, oxygen-enriched air and oxygen-deficient air.
13. Titanium silicon molecular sieve prepared according to the method according to any one of claims 5 to 12.
14. Use of the titanium silicon molecular sieve according to any one of claims 1 to 4 and 13 in catalyzing organic reactions.
Citation Information
Patent Citations
Halogen-containing titanium silicalite molecular sieve and preparation method thereof
CN115724439A
Preparation method for Ti-Si molecular sieve
CN1260241A